2015
DOI: 10.1002/jbm.b.33547
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric scaffolds in tissue engineering: a literature review

Abstract: The tissue engineering scaffold acts as an extracellular matrix that interacts to the cells prior to forming new tissues. The chemical and structural characteristics of scaffolds are major concerns in fabricating of ideal three-dimensional structure for tissue engineering applications. The polymer scaffolds used for tissue engineering should possess proper architecture and mechanical properties in addition to supporting cell adhesion, proliferation, and differentiation. Much research has been done on the topic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
157
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(165 citation statements)
references
References 96 publications
(256 reference statements)
2
157
0
2
Order By: Relevance
“…This important issue indicates that histologic analysis is mandatory in evaluating new bone volume. Scaffold porosity and pore interconnectivity are important for cell migration and vascular tissue ingrowth (28); previous studies have shown that pore size between 100 and 400 mm is optimal for bone ingrowth (29). The Col-Ap nanocomposite has a pore size of 142.2 AE 25.5 mm, with more interconnective spaces than b-TCP.…”
Section: Discussionmentioning
confidence: 98%
“…This important issue indicates that histologic analysis is mandatory in evaluating new bone volume. Scaffold porosity and pore interconnectivity are important for cell migration and vascular tissue ingrowth (28); previous studies have shown that pore size between 100 and 400 mm is optimal for bone ingrowth (29). The Col-Ap nanocomposite has a pore size of 142.2 AE 25.5 mm, with more interconnective spaces than b-TCP.…”
Section: Discussionmentioning
confidence: 98%
“…Although the minimum pore size needed for bone ingrowth still remain a challenging issue, a value of 75–100 µm has been reported by many researchers [65]. However, it has been shown that osteogenesis could be enhanced with pore sizes larger than 300 µm [66]. By studying the effects of pore size of 3DP TCP scaffolds on human fetal osteoblasts, it has been demonstrated that proliferation rate of cells increases with decrease in designed pore size from 1000 to 750 and 500 µm [67].…”
Section: Discussionmentioning
confidence: 99%
“…Cell adhesion, migration and proliferation processes are related to micro/mesopores while macropores are related to processes of diffusion of bioactive substances and nutrients. 23 The results obtained in the characterization of the ceramics show an equitable distribution of macro, meso, and micropores and indicate their suitability for using as an antibiotic vehicle. In relation with BET analysis, there are no significant differences although the SSA increases as the Si content increases.…”
Section: Discussionmentioning
confidence: 88%
“…Porosity and pore size in ceramics and cements are directly related to the regeneration of tissues. Cell adhesion, migration and proliferation processes are related to micro/mesopores while macropores are related to processes of diffusion of bioactive substances and nutrients . The results obtained in the characterization of the ceramics show an equitable distribution of macro, meso, and micropores and indicate their suitability for using as an antibiotic vehicle.…”
Section: Discussionmentioning
confidence: 96%